2015
DOI: 10.1002/jaba.232
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of differential reinforcement procedures with children with autism

Abstract: The current evaluation compared the effects of 2 differential reinforcement arrangements and a nondifferential reinforcement arrangement on the acquisition of tacts for 3 children with autism. Participants learned in all reinforcement-based conditions, and we discuss areas for future research in light of these findings and potential limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…The asterisk represents the session differential reinforcement was initiated in the early and late onset conditions. efficiency relative to nondifferential reinforcement (e.g., Hausman et al, 2014;Karsten & Carr, 2009), but the most efficient differential reinforcement arrangement may differ across individuals (e.g., Boudreau et al, 2015) and tasks (Johnson et al, 2017). However, no research has directly evaluated when during instruction to begin differentially reinforcing unprompted and prompted correct responses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The asterisk represents the session differential reinforcement was initiated in the early and late onset conditions. efficiency relative to nondifferential reinforcement (e.g., Hausman et al, 2014;Karsten & Carr, 2009), but the most efficient differential reinforcement arrangement may differ across individuals (e.g., Boudreau et al, 2015) and tasks (Johnson et al, 2017). However, no research has directly evaluated when during instruction to begin differentially reinforcing unprompted and prompted correct responses.…”
Section: Resultsmentioning
confidence: 99%
“…Differential reinforcement, in relation to skill acquisition, consists of arranging higher quality, larger magnitude, or denser schedules of reinforcement for unprompted correct responses, while delivering lower quality, smaller magnitude, or leaner schedules of reinforcement for prompted correct responses (Johnson, Vladescu, Kodak, & Sidener, 2017). Although the use of differential reinforcement has been recommended by researchers (e.g., Grow & LeBlanc, 2013) and early intervention manuals (e.g., Leaf & McEachin, 1999;Lovaas, 2003), only eight studies have evaluated differential reinforcement during skill acquisition programs with individuals with autism and other developmental disabilities (Boudreau, Vladescu, Kodak, Argott, & Kisamore, 2015;Cividini-Motta & Ahearn, 2013;Fiske et al, 2014;Hausman, Ingvarsson, & Kahng, 2014;Johnson et al, 2017;Karsten & Carr, 2009;Olenick & Pear, 1980;Touchette & Howard, 1984). A subset of these studies evaluated the efficiency of one differential reinforcement arrangement (i.e., reinforcement quality or schedule) compared to nondifferential reinforcement (Hausman et al, 2014;Karsten & Carr, 2009;Olenick & Pear, 1980;Touchette & Howard, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from the current and previous studies raise interesting questions as to how practitioners should select a teaching arrangement that most efficiently produces acquisition and generalized outcomes. Previous research has shown that the most efficient instructional arrangement is often learner‐specific (e.g., Boudreau, Vladescu, Kodak, Argott, & Kisamore, ; Koehler, Iwata, Roscoe, Rolider, & O'Steen, ). If this is the case, future research should attempt to delineate the variables that influence learner‐specific response patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment‐based instruction provides a method for examining the efficacy of interventions prior to implementing them in practice. Assessments are used to determine which types of prompts to provide during instruction (e.g., Seaver & Bourret, ), the efficacy and efficiency of prompt‐fading strategies (e.g., Libby, Weiss, Bancroft, & Ahearn, ; Seaver & Bourret, ), efficient error‐correction strategies (e.g., Carroll, Joachim, St. Peter, & Robinson, ; McGhan & Lerman, ), and how to arrange consequences for independent and prompted correct responses (e.g., Boudreau, Vladescu, Kodak, Argott, & Kisamore, ). These assessments are needed to identify how to arrange instruction because the most efficacious and efficient instructional strategies often differ across individuals.…”
Section: Introductionmentioning
confidence: 99%